Comparison of taxation of personal income in Canada and the Czech Republic - Písecká, Renáta; Finardi, Savina; Kolek, Daniel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This diploma thesis deals with personal income taxation in Canada, its tax system and legislative procedures. However, the main aim of this thesis is to compare personal income taxation in Canada and the Czech Republic, to which is mainly devoted the last part of the first chapter and then second half of the thesis. The final part consists of using a model example for the practical application of various tax rules in different countries. It also evaluates whether it would be beneficial and feasible to apply certain procedures and rules used for calculating personal income tax in Canada to the context of the Czech Republic.
Vedoucí práce: Savina Finardi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: zdanění a daňová politika [obor dipl. práce]; diplomové práce; master's theses